Gap Junction Enhancer Increases Efficacy of Cisplatin to Attenuate Mammary Tumor Growth - Shishido, Stephanie N. (Public Library of Science, 2012)
Cisplatin treatment has an overall 19% response rate in animal models with malignant tumors. Increasing gap junction activity in tumor cells provides the targets to enhance antineoplastic therapies. Previously, a new class of substituted quinolines (PQs) acts as gap junction enhancer, ability to increase the gap junctional intercellular communication, in breast cancer cells. We examined the effect of combinational treatment of PQs and antineoplastic drugs in an animal model, showing an increase in efficacy of antineoplastic drugs via the enhancement of gap junctions. Mice were implanted with estradiol-17ß (1.7 mg/pellet) before the injection of 1×10(7) T47D breast cancer cells subcutaneously into the inguinal region of mammary fat pad. Animals were treated intraperitoneally with DMSO (control), cisplatin (3.5 mg/kg), PQ (25 mg/kg), or a combining treatment of cisplatin and PQ. Cisplatin alone decreased mammary tumor growth by 85% while combinational treatment of cisplatin and PQ1 or PQ7 showed an additional reduction of 77% and 22% of tumor growth after 7 treatments at every 2 days, respectively. Histological results showed a significant increase of gap junction proteins, Cx43 and Cx26, in PQ-treated tissues compared to control or cisplatin. Furthermore, evidence of highly stained caspase 3 in tumors of combinational treatment (PQ and cisplatin) was seen compared to cisplatin alone. We have showed for the first time an increase in the efficacy of antineoplastic drugs through a combinational treatment with PQs, a specific class of gap junction enhancers.